A randomized controlled trial of sublingual Misoprostol - 600µg versus intravenous Oxytocin - 10IU in prevention of post partum hemorrhage during cesarean section - Yaliwal, Rajasri G.; Bidri, Shailaja R.; Navani, Ashwini S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Mortality related to pregnancy and childbirth causes half a million women around the world to die annually. About 35% of these deaths are from postpartum hemorrhage (PPH). Prevention of PPH has been advised by the WHO by the use of Oxytocin 10 IU IM or IV and Misoprostol 600 µg in low resource settings in vaginal delivery. However there have been only a few reports on the use of Misoprostol during cesarean section. The best route and dose of Misoprostol is still being debated. Methods: One hundred women with term singleton pregnancy undergoing elective or emergency cesarean section under spinal anesthesia were randomly allocated to receive either Misoprostol 600µg sublingually or intravenous oxytocin 10 IU soon after delivery of the baby. Estimated blood loss and comparative change in preoperative hemoglobin to post operative hemoglobin levels and side effects were evaluated. Results: Blood loss was found to be more in Misoprostol than Oxytocin. Eight patients of the Misoprostol group required additional oxytocics. Oxytocin group did not receive any additional drugs. No surgical intervention was made in either of the groups. The most common side effect with Misoprostol was shivering (46%) and in Oxytocin group fever (4%). Conclusions: Sublingual Misoprostol of 600µg works to prevent postpartum bleeding. In our study Oxytocin was more effective than Misoprostol in preventing PPH during cesarean section. Late onset of action of Misoprostol in comparison to Oxytocin may render suturing of the uterus difficult due to pooling of blood. In settings in which use of Oxytocin is not feasible, Misoprostol might be a suitable alternative for post-partum hemorrhage.